TINGKAT KESULITAN KONSEPTUAL DAN PRAKTIS DALAM PEMBELAJARAN KIMIA: STUDI DI SMA NEGERI 6 MEDAN (Sindoro: Cendikia Pendidikan, 2025)
This study aims to analyze the level of difficulty experienced by students in understanding the concepts and practices of chemistry learning at SMA Negeri 6 Medan. The method used is descriptive quantitative with a survey approach through questionnaires and interviews. The results showed that 68% of students experienced difficulties in contextual aspects (such as stoichiometry and chemical bonds), while 57% of students experienced difficulties in laboratory practicums. The main causal factors are lack of basic understanding, less varied learning methods, and limited laboratory facilities. This study recommends the use of a contextual learning approach and improving supporting facilities for practicums to reduce student difficulties.